2004
DOI: 10.1021/ja046248w
|View full text |Cite
|
Sign up to set email alerts
|

Catalaytic Isomerization of 1,5-Enynes to Bicyclo[3.1.0]hexenes

Abstract: Transition metal-catalyzed isomerization and rearrangement reactions of unsaturated systems provide access to structural motifs not accessible through their thermal counterparts. This is exemplified by the numerous applications of transition metal-catalyzed Alder-ene reactions of 1,6-and 1,7-enynes for the synthesis of cyclopentyl and cyclohexyl ring systems. 1 The corresponding skeletal rearrangements of simple 1,5-enynes are much less studied. Berson and co-workers conjectured that the thermal rearrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
122
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(140 citation statements)
references
References 22 publications
9
122
0
7
Order By: Relevance
“…[39] Scheme 48 summarizes the studies of Toste and coworkers. [38] Unlike the two previous reports, which utilized exclusively C(3)-acyloxy-and hydroxy-substituted enynes, Toste and co-workers found that gold catalysis of the 1,5-enyne cycloisomerization enabled efficient conversions of enynes bearing aryl and alkyl groups at the C(3) position. In a typical experiment, subjection of enyne 219 to 1 mol % of cationic gold- In 2004, Nishibayashi and co-workers also reported a sequential reaction transforming 1,5-enyne, which was generated in situ from a propargyl alcohol, to a bicycloA C H T U N G T R E N N U N G [3.1.0]hexene skeleton by tandem Ru and Pt catalysis.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [310]alkmentioning
confidence: 84%
See 1 more Smart Citation
“…[39] Scheme 48 summarizes the studies of Toste and coworkers. [38] Unlike the two previous reports, which utilized exclusively C(3)-acyloxy-and hydroxy-substituted enynes, Toste and co-workers found that gold catalysis of the 1,5-enyne cycloisomerization enabled efficient conversions of enynes bearing aryl and alkyl groups at the C(3) position. In a typical experiment, subjection of enyne 219 to 1 mol % of cationic gold- In 2004, Nishibayashi and co-workers also reported a sequential reaction transforming 1,5-enyne, which was generated in situ from a propargyl alcohol, to a bicycloA C H T U N G T R E N N U N G [3.1.0]hexene skeleton by tandem Ru and Pt catalysis.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [310]alkmentioning
confidence: 84%
“…[36,37] These reports were soon followed by a communication from the Toste laboratory, describing a series of independently observed cycloiso- merizations of 1,5-enynes, which were catalyzed by cationic gold-phosphine complexes. [38] Fürstner and co-workers reported that subjection of enyne 200 to a catalytic amount of PtCl 2 in toluene at 60 8C afforded bicyclic ketone 201 in 75 % yield (Scheme 44). [36] The deuterium label in the product appeared exclusively at the C (2) The studies of Malacria and co-workers are summarized in Scheme 46 and Scheme 47.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [310]alkmentioning
confidence: 99%
“…[321,322] Sofern die neu gebildete Cyclopropylgruppe ihrerseits an der Reaktion teilnimmt [Schema 69, Gl. (2) [323] Auch die in manchen Cycloisomerisierungen von 1,5-Eninen beobachteten Cyclopentene erklären sich aus einem Mechanismus mit 1,2-Alkylverschiebung, wobei während der Ringerweiterung lediglich eine andere Bindung der Cyclopropyleinheit gebrochen wird (359!361).…”
Section: Angewandte Chemieunclassified
“…金的配合物催化的有机反应得到了广泛的研究, 已 经能够使许多反应在温和的条件下进行, 且具有较高的 产率和化学选择性 [9] . 目前, 金的配合物催化的反应有 烯烃炔烃的环化反应 [10] 、炔烃的氢化氨基化反应 [11] , 炔 烃的水合反应 [12] 等, 在国内也有一些关于金配合物催 化有机反应的研究, 如 Friedel-Crafts 烷基化反应 [13] , 烯 烃的胺基芳基化反应 [14] 等. 本课题组此前合成了一系 列新型茚基膦配体, 并用于钯催化 C-N 偶联反应 [15,16] , 水相中的 C-C 偶联反应 [17] 以及钌催化的醇脱氢反应 [18] 等 .…”
unclassified